The Effects of Communicative Source and Dynamics on the Maintenance and Accessibility of Longer‐term Memories: Applications to Sexual Abuse and Its Public Disclosure. Issue 6 (November 2015) - Fagin, Martin M.; Cyr, Travis G.; Hirst, William
Summary: Recent public testimony concerning sexual abuse on the part of celebrities raises the question of what happens to memories when they enter the public domain. The present paper reviews research on the effects of communication on memory and examines how the context of this communication affects its influence on memory, both in the short and long term. Specifically, we discuss how communication with the self, a small group, and the larger public affects the content and availability of different elements of both emotional and more mundane memories, in the short term and in the long term. Evidence suggests that, although forgetting is rapid in the first few years, it then levels off. Although this pattern would suggest that the effects conversational influences have on memory may be limited to the first few years, the present paper argues that the pattern will vary as the source changes.Copyright © 2015 John Wiley & Sons, Ltd.